Law for business - Barnes, A. James , 1942-; Dworkin, Terry Morehead; Richards, Eric L. (McGraw-Hill/Irwin, 2009)
Offers a treatment of the legal issues of importance to business students and the business profession. This book uses such techniques as content summaries to apply concepts to practice